PENGARUH KEPERCAYAAN DAN TIPE STANDAR (US GAAP DAN IFRS) TERHADAP KEPUTUSAN INVESTOR NON PROFESIONAL - Elyastuti, Cintya Cindy; Handoko, Jesica (Jurnal Akuntansi Kontemporer, 2015)
Non-professional investor decisions are influenced by various factors. This experimental research is using 2x2 between subjects factorial design that aims to investigate the influence of type of standards (US GAAP and IFRS) and trust of the financial report-ing system to the decision of non-professional investors. Type of standard and trust of the financial reporting system are use to be independent variables, where the type of accounting standards is manipulated variable and trust of the financial reporting system is a measured variable. The instrument in this study using the example of experimental materials by Bailey and Sawers (2012) that adapted by researchers. Sixty-seven students magister of accounting (S2) Airlangga University Surabaya who analyzed two simi-lar companies are presented using either rules-based (US GAAP) and principles- based (IFRS) are available and complete. The analysis technique for hypothesis testing using Analysis of Variance (ANOVA) and t test. Results of the study after the trust are classified into more trust and less trust shows that the type of standard or trust alone does not affect investment decisions (alloca-tion of investment funds). Interaction between type of standard and trust influence investment decisions. However, non-professional investors are more trust and less trust in the current financial reporting system does not provide a different decision on the financial statements which use the principles-based and rules-based standards.